Effects of gestational exposure to di-n-butyl phthalate and mineral oil on testis development of the Mongolian gerbil - Christante, C. M.; Pinto-Fochi, M. E. [UNESP]; Negrin, A. C.; Taboga, S. R. [UNESP]; Goes, R. M. [UNESP] (Csiro Publishing, 2018)
Phthalate esters are endocrine disrupters that can affect the development of the testis in a species-specific manner. However, their interference in the male gonads of the Mongolian gerbil is unknown. The aim of the present study was to evaluate whether gestational exposure to di-n-butyl phthalate (DBP) interferes with the development of the gerbil testis during the first six weeks of life. Males were evaluated at 1, 7,14, 28, 35 and 42 days of age in an untreated (control) group or groups exposed from 8 to 23 days gestation to DBP (100 mg kg(-1) day(-1) in mineral oil) or vehicle by maternal gavage. DBP exposure impaired cell proliferation within the seminiferous cords at birth, but increased proliferation at the end of the first week, when higher testosterone concentrations were observed. The vehicle (mineral oil) reduced the total number of gonocytes and attenuated the decrease in testosterone concentrations at 7 days. The vehicle also altered gonocyte relocation at 14 days and increased oestrogen concentrations at 28 days by approximately 112%. In summary, both DBP and oil interfered in gonadal development and testosterone plasma concentrations in the first week of postnatal life. However, the changes observed at the beginning of puberty were not seen after exposure to DBP, indicating a more harmful effect of mineral oil in this period.
Keywords: endocrine disruptor; germ cell differentiation; number of gonocytes; plasma oestrogen concentration; steroidogenesis